Teacher Social-Emotional Competence: Exploring Self-Awareness and Professional Reflection Challenges - Deny Hadi Siswanto; Kintoko; M.M. Endang Susetyawati; Muhammad Yusuf Rambe (Jurnal Pendidikan dan Inovasi Pembelajaran, 2026)
This study aims to examine teachers’ social-emotional competence at SMA Muhammadiyah Mlati, including self-awareness, emotional regulation, social skills, empathy, and responsible decision-making. This research employed a descriptive qualitative method. Data were collected through interviews, observations, and documentation involving teachers and students selected through purposive sampling. Data were analyzed through reduction, presentation, and conclusion drawing. The findings show that teachers’ social-emotional competence has developed well. Teachers are able to recognize their emotions, manage stress positively, build humanistic relationships with students, and make pedagogical decisions by considering students’ psychological conditions. However, challenges remain in the inconsistency of deep self-reflection and the dominance of administrative tasks. This study concludes that continuous reinforcement through stress management training and a systematic reflective culture is needed to optimize the quality of learning.